Reincorporating Friedrich von Wieser and the concept of power into the Austrian research program - Stefan Kolev (Duke University, Center for the History of Political Economy (CHOPE), 2017)
This paper constitutes the start of a project dedicated to Austrian economist and economic sociologist Friedrich von Wieser (1851-1926). Its central claim is that especially in recent decades, Wieser has become a disproportionately underresearched scholar, and the paper provides a set of arguments why this is unjustified. Wieser's life and work are portrayed along five dimensions: the innovative social scientist (section 2); the erector of the Austrian School in its formative decades (section 3); the synthesizer of socio-economic ideas (section 4); the teacher to whom scientific credit has been granted undeservedly seldom (section 5); finally, the connector to other contemporaneous paradigms of economics and economic sociology, especially the ones of Max Weber and Vilfredo Pareto (section 6). The paper sets up a meta-presentation of a set of questions that appear crucial at this stage of the project. In subsequent sub-projects, the five above dimensions will be expanded into separate but interdependent expositions. As an example for the initiation of such a sub-project, Wieser's concept of power - a key topos also for the other members of the Viennese "triumvirate" - is revisited (section 7). Since later generations of the Austrian School have been reluctant to use this concept in their systems, this and later inquiries will explore how central Austrian concepts like "spontaneous order" or "human action" may need a reformulation if power relations are explicitly built into the analysis. While the project is primarily conducted as a history of economics endeavor, revisiting Wieser's legacy in general and the significance of power in particular also aims at generating impulses for the further development of the research program of Austrian economics, as well as at a better understanding of the increasing politico-economic fragility and instability of today's Western democracies, phenomena related to power and leadership.
Keywords: A11; B13; B25; B31; P16; Z13; 330; Friedrich von Wieser; Joseph A. Schumpeter; Ludwig von Mises; F.A. Hayek; Max Weber; Austrian School; economic sociology; power